Improving Health Protocols and Marketing of Baked Bread Umkm Products in Diro Hamlet, Bantul - Idiani Darmawati; Ratna Indriawati; Iswanto Suwarno (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the fields that make a significant contribution to spurring Indonesia's economic growth. This is because the absorption capacity of MSMEs for a workforce is very large and close to the small people. Toast is one food that is quite popular at all ages. Consumers can choose a variety of flavors that suit their tastes. This type of food can be found in several places, including in the hamlet of Diro Bantul. One of the toast seller groups is chaired by Mr. Pungki Priawan, who has been selling toast since 2016. The problems faced are during this pandemic, sales turnover has decreased drastically, the lack of an understanding of the importance of carrying out an online marketing strategy, has not been able to adjust to the pandemic conditions which must implement health protocols according to government recommendations, so that business results cannot reach the maximum. . The UMY Service Team aims to improve the skills of SME players so that they can create digital promotional media to market products online and help provide education on Health protocols, so that they are more hygienic and increase sales turnover. The target of this community service is in the form of increasing discipline in implementing health protocols and helping create digital promotions for online sales through social media accounts. The method used is direct online and offline assistance as well as providing health protocol education. The results obtained during the mentoring were very significant, where since an online marketing strategy was created, sales turnover has increased rapidly, and since the education from the service team, business actors are more disciplined in implementing health protocols.